The BTBR T+tf/J mouse model for autism spectrum disorders–in search of biomarkers - Meyza, Ksenia Z.; Defensor, Erwin B.; Jensen, Ashley L.; Corley, Michael J.; Pearson, Brandon L.; Pobbe, Roger L.H.; Bolivar, Valerie J.; Blanchard, D. Caroline; Blanchard, Robert J. (Behavioural brain research, 2013)
► The BTBR T+tf/J mouse is an animal model of autism spectrum disorders with strong face validity. ► The neuroanatomy and physiology of the BTBR mouse resembles that of some individuals with ASD. ► Lack of corpus callosum and impaired synaptogenesis and neurogenesis may be linked with heparan sulfate reduction. ► The glutamatergic transmission seems crucial for restoring sociability of BTBR mice. Autism spectrum disorders (ASD) form a common group of neurodevelopmental disorders appearing to be under polygenic control, but also strongly influenced by multiple environmental factors. The brain mechanisms responsible for ASD are not understood and animal models paralleling related emotional and cognitive impairments may prove helpful in unraveling them. BTBR T+tf/J (BTBR) mice display behaviors consistent with the three diagnostic categories for ASD. They show impaired social interaction and communication as well as increased repetitive behaviors. This review covers much of the data available to date on BTBR behavior, neuroanatomy and physiology in search for candidate biomarkers, which could both serve as diagnostic tools and help to design effective treatments for the behavioral symptoms of ASD.